Predicting Skin Permeation-enhancing Effect of Fixed Oils Using Saturated to Unsaturated Fatty Acid Ratio Content (Nigerian Journal of Pharmaceutical Research, 2024)
Background: Transdermal drug delivery is non-invasive and advantageous as it improves patient compliance.Objective: This study evaluated the effect of varying ratios of saturated to unsaturated fatty acids in fixed oils on the permeation of ibuprofen across pig dorsal skin.Methods: The solubility of ibuprofen in soybean oil, theobroma oil, and shea butter (fixed oils) was evaluated and in vitro skin permeation studies were conducted using Franz diffusion cells.Results: A significant difference in permeability parameters, such as flux and effective skin permeability, in the different formulations was observed. Skin permeation depended on the ratio of saturated to unsaturated fatty acids. It also depended on the type and concentration of individual saturated and unsaturated fatty acids present in the fixed oils. The skin permeation of ibuprofen increased with an increasing ratio of palmitic acid (PA) to oleic acid (OA) concentrations. The highest flux was obtained in the theobroma oil formulation, with a PA:OA ratio of 0.78. The lowest flux was obtained in the shea butter formulation, with a PA:OA ratio of 0.09. The PA:OA ratio was 0.46 in the soybean oil formulation.Conclusion: These results suggest that the ratio of saturated to unsaturated fatty acids in fixed oils could be used as a model for predicting the rate of skin permeation of drugs in oil-based formulations. Depending on the desired rate of drug permeation, different combinations of the ratio of saturated to unsaturated fatty acids can be used in formulations for transdermal delivery.
Keywords: Fixed oils; ibuprofen; saturated fatty acids; unsaturated fatty acids; transdermal delivery